Region-specific role of growth differentiation factor-5 in the establishment of sympathetic innervation. Issue 1 (December 2016) - O'Keeffe, Gerard; Gutierrez, Humberto; Howard, Laura; Laurie, Christopher; Osorio, Catarina; Gavaldà, Núria; Wyatt, Sean; Davies, Alun
Abstract Background Nerve growth factor (NGF) is the prototypical target-derived neurotrophic factor required for sympathetic neuron survival and for the growth and ramification of sympathetic axons within most but not all sympathetic targets. This implies the operation of additional target-derived factors for regulating terminal sympathetic axon growth and branching. Results Here report that growth differentiation factor 5 (GDF5), a widely expressed member of the transforming growth factor beta (TGFβ) superfamily required for limb development, promoted axon growth from mouse superior cervical ganglion (SCG) neurons independently of NGF and enhanced axon growth in combination with NGF. GDF5 had no effect on neuronal survival and influenced axon growth during a narrow window of postnatal development when sympathetic axons are ramifying extensively in their targets in vivo. SCG neurons expressed all receptors capable of participating in GDF5 signaling at this stage of development. Using compartment cultures, we demonstrated that GDF5 exerted its growth promoting effect by acting directly on axons and by initiating retrograde canonical Smad signalling to the nucleus. GDF5 is synthesized in sympathetic targets, and examination of several anatomically circumscribed tissues inGdf5 null mice revealed regional deficits in sympathetic innervation. There was a marked, highly significant reduction in the sympathetic innervation density of the iris, a smaller though significant reduction in the trachea, but no reduction in the submandibular salivary gland. There was no reduction in the number of neurons in the SCG. Conclusions These findings show that GDF5 is a novel target-derived factor that promotes sympathetic axon growth and branching and makes a distinctive regional contribution to the establishment of sympathetic innervation, but unlike NGF, plays no role in regulating sympathetic neuron survival.